Интеллект и действие - Суименко, Е. (Социология: теория, методы, маркетинг, 2007)
The genre of article is a fragmented essay. It interprets the social sense of such elementary and opposite by their meanings principles of human life as intellect and action. As the author believes, the correlation and interaction of these principles in society may have two probable outcomes. On the one hand it may cause dying down of human actions in intellect. On the other hand it may provoke the human transition from 'prehistory' to the 'true history'. Finally, the author outlines the argument that alternatives of the social development are linked to Vernadsky's noosphere concept.